Tingkat Pengetahuan dan Pemahaman Mahasiwa Dalam Menggunakan Aplikasi SPSS Untuk Mata Kuliah Biostatistik - Pasaribu, Angelia; Jetslin Simbolon (MAMEN: Jurnal Manajemen, 2022)
Biostatistics is the application of statistics in the field of Medical Records and Health Information (RMIK). Data used as accurate information material is usually taken from raw data that has been processed and then presented as statistics in the form of tables and graphs or other forms of reports. Data presentation is an activity that collects various information and is then compiled, thus providing conclusions and taking actions.This study aims to help determine the level of knowledge of students of the Health information management study program in analyzing and testing data using the SPSS application at the STIKes Santa Elisabeth Medan campus. The population used is all students of the Health Information Management study program level 1 with a total sample of 9 people. This type of research is a descriptive study whose purpose is to present the picture to be studied. The instrument used is a questionnaire. Analyze data descriptively.